(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mahulette AS, Alfian A, Suyadi, Supriyanto, Situmorang J, Matatula AJ, Kilkoda AK, Nendissa JI, Wattimena AY. 2022. Type and morphological character of local clove (Syzygium aromaticum) from Maluku, Indonesia. Biodiversitas 23: 1301-1309. Maluku Islands are known as the origin for the distribution of cloves (Syzygium aromaticum L.) in the world, where the diversity of clove germplasm is high. So far, information on the diversity of local clove morphology in Maluku is still very limited. The study was aimed to characterize the morphological diversity of local clove accessions in Maluku. The study was conducted in three distribution areas in Maluku, namely Ambon Island, Seram Island, and Haruku Island. Characterization was carried out on 130 local clove accessions of Maluku based on 32 morphological characters. The exploration identified nine types of cloves, namely Tuni, Forest Clove, Raja, Boiselang, Zanzibar, Bogor, Jinten, Tae, Damar, and three variants of Forest Clove, two variants of Raja, and two variants Zanzibar. Forest cloves, Raja, Boiselang Jinten, Tae, Damar are classified as wild-type cloves, while Tuni, Zanzibar and Bogor cloves are classified as cultivated cloves. The Hierarchical Cluster Analysis (HCA) obtained 2 large groups of local cloves with 57% agro-morphological differences. The first group is Forest Clove and Boiselang, while the second group is other local clove accessions (Tuni, Jinten, Red Zanzibar, White Zanzibar, Bogor, Damar, Tae, and Raja). The Principle Component Analysis (PCA) shows a total diversity of 66.7% with 4 characters based on grouping. These cloves are also categorized into wild type, cultivated, aromatic, and non-aromatic types.